A Multifunctional Trypsin Protease Inhibitor from Yellow Bell Pepper Seeds: Uncovering Its Dual Antifungal and Hypoglycemic Properties - Cotabarren, Juliana (2023)
Fungal infections are a growing public health concern worldwide and the emergence of antifungal resistance has limited the number of therapeutic options. Therefore, developing novel strategies for identifying and developing new antifungal compounds is an active area of research in the pharmaceutical industry. In this study, we purified and characterized a trypsin protease inhibitor obtained from Yellow Bell Pepper (Capsicum annuum L.) seeds. The inhibitor not only showed potent and specific activity against the pathogenic fungus Candida albicans, but was also found to be non-toxic against human cells. Furthermore, this inhibitor is unique in that it also inhibits -1,4-glucosidase, positioning it as one of the first plant-derived protease inhibitors with dual biological activity. This exciting discovery opens new avenues for the development of this inhibitor as a promising antifungal agent and highlights the potential of plant-derived protease inhibitors as a rich source for the discovery of novel multifunctional bioactive molecules.